Branch Retinal Vein Occlusion in a Case of Sarcoidosis - Shrestha, Ruchi; Kharel Sitaula, Ranju; Karki, Pratap; Narayan Joshi, Sagun (Nepalese Journal of Ophthalmology, 2021)
Abstract: Background: Sarcoidosis is a chronic inflammatory disorder characterized by non-caseation granuloma. It is an inflammatory disorder of unknown etiology. Sarcoidosis has variable ocular presentations from anterior uveitis to rare venous occlusions. Case: We present a rare case of sarcoidosis with bilateral hilar lymphadenopathy and a compatible uveitis. Positive findings of mutton fat keratic precipitates, Koeppes nodule, posterior synechiae, trabecular meshwork nodules, Candle wax dripping sign, Branch retinal vein occlusion and choroidal granuloma in one eye supported the diagnosis of sarcoidosis. Elevated serum acetylcholine esterase and bilateral hilar lymphadenopathy also confirmed the diagnosis of sarcoidosis. Observation: The patient responded well to oral steroids and laser photocoagulation of the vein occlusion area. The patient developed complications of steroid like Herpes Zooster of abdomen and avascular necrosis of femur. Conclusion: Branch Retinal Vein Occlusion is a rare vascular complication in ocular sarcoidosis. Systemic steroids and laser for vein occlusion is mainstay of treatment. Physician must be aware of serious complications of steroid therapy, as seen in this case. Keyword: Sarcoidosis, Branch retinal vein occlusion, Steroids.